Estrés laboral y su relación con el desempeño profesional en el personal de enfermería del Hospital II-2 Tarapoto. Abril - Julio 2013 - Díaz Reátegui, Ivonne del Pilar (2013)
In order to determine the relationship between job stress and job performance, how are you working situations cause discomfort in nurses working in services emergency, medicine, pediatrics, surgery and obstetrics Hospital II - 2 Tarapoto. Established a research study descriptive correlational level, with qualitative and quantitative approach, cross-sectional, with prospective data collection, whose population consisted of 60 nurses, the same that formed the sample to 100%. To larecolección data on occupational stress was used the survey technique, which fueronanalizados criteria of descriptive statistics, tables represented in frequency division ygráficos. The instrument used to identify job stress was the questionnaire " The Nursing Stress Scale - NSS " written by Pamela Gray Toft and James Anderson, validated and standardized by WHO - World Health Organization, with Cronbach's Alpha 0.953, measured the frequency with which certainsituations are perceived as stressors (physical, psychological and social) by hospital nursing staff according to the Likert scale 0-3 points (very often, often, sometimes, and never). To collect data on job performance was used non-participant observation technique, developed a format that allowed assess professional performance level (low, medium and high) of the nursing staff through three skills (cognitive, attitudinal - social and technical capacity), according to the Likert scale of 0-3 points (always, often, sometimes, and never), validated through a test pilotocon 22 nurses Hospital - Health is Tarapoto, who met similar to the study population. The result was that 28.3 % of the study population will produce certain work situations affecting stress in their professional performance. Being the 10.0 % with work stress and low level of professional performance, while 18.3 % with job stress and average level of professional performance, with p = 0.003, x2=11,395. We conclude that there is significant relationship between job stress and job performance of nurses Hospital II -2 Tarapoto in the period from April to July of 2013.